Living with limb loss: everyday experiences of "good" and "bad" days in people with lower limb amputation. Issue 20 (25th September 2019) - Day, Melissa Catherine; Wadey, Ross; Strike, Siobhan
Abstract: Purpose: To provide an understanding of the everyday experiences of individuals with a limb amputation. Methods: Twenty-two participants (14 female, 8 male) with a mean-age of 42 years ( SD = 10 years) were recruited to take part in two focus groups. The participants reported a range of lower-limb amputations (i.e., congenital, acquired, transfemoral, trantibial, unilateral, and bilateral) and on an average were 5 years post-surgery ( SD = 7 years). Each focus group comprised of 11 participants and was moderated by either the first or second author. The moderator asked participants to discuss their everyday experiences of life with an amputation using Charmaz's good day/bad day approach. Focus groups were transcribed verbatim and analyzed using an inductive thematic analysis. Results: Four themes were identified: pain, organization and planning, the embodied experience after amputation, and interactions with others. Conclusions: These themes provide a key resource for understanding daily fluctuations in physical, social, and psychological functioning. Implications for Rehabilitation: Lower limb amputation can result in daily fluctuations in physical, social, and psychological functioning. These fluctuations can be illustrated through experiences of pain, planning and organization, embodied experiences, and interactions with others. At a policy level, evaluations of daily living after an amputation should be based on a longitudinal assessment.